2016
DOI: 10.1371/journal.pone.0160056
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Facial Emotion Recognition between First Episode Psychosis, Borderline Personality Disorder and Healthy Controls

Abstract: BackgroundFacial emotion recognition (FER) is essential to guide social functioning and behaviour for interpersonal communication. FER may be altered in severe mental illness such as in psychosis and in borderline personality disorder patients. However, it is unclear if these FER alterations are specifically related to psychosis. Awareness of FER alterations may be useful in clinical settings to improve treatment strategies. The aim of our study was to examine FER in patients with severe mental disorder and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
30
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 53 publications
5
30
2
2
Order By: Relevance
“…Interestingly, face recognition performance of BPD patients was more severely impaired when faces were presented after a negative emotional prime, which confirms stronger influences of emotional information on interpersonal emotion processing in BPD. A more negative processing of neutral, ambiguous, or positive emotional faces was also reported in several other recent studies with relatively large groups of female BPD patients and matched healthy control groups (e.g., Catalan et al [9], Daros et al [10], Izurieta Hidalgo et al [11], Thome et al [12], and van Dijke et al [13]; however, see Lowyck et al [14] where now alterations could be found). Confirmation for a threat hypersensitivity also comes from recent eye-tracking studies, which showed faster and more initial eye movements towards the eyes of angry faces and an inability to disengage attention from fearful eyes in BPD patients [15, 16].…”
Section: Recent Behavioral Findingssupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, face recognition performance of BPD patients was more severely impaired when faces were presented after a negative emotional prime, which confirms stronger influences of emotional information on interpersonal emotion processing in BPD. A more negative processing of neutral, ambiguous, or positive emotional faces was also reported in several other recent studies with relatively large groups of female BPD patients and matched healthy control groups (e.g., Catalan et al [9], Daros et al [10], Izurieta Hidalgo et al [11], Thome et al [12], and van Dijke et al [13]; however, see Lowyck et al [14] where now alterations could be found). Confirmation for a threat hypersensitivity also comes from recent eye-tracking studies, which showed faster and more initial eye movements towards the eyes of angry faces and an inability to disengage attention from fearful eyes in BPD patients [15, 16].…”
Section: Recent Behavioral Findingssupporting
confidence: 74%
“…Contrary to this, Nicol et al [29] found a significant correlation between self-reported childhood traumatization and deficits in the recognition of facial disgust, an emotion, which was neither included in the study of Veague and Hooley [22] nor in our own experiment, among a group of BPD patients. Furthermore, Catalan et al [9] recently found a very similar negativity bias in facial emotion recognition in a large group of patients with a first-episode psychosis and patients with BPD compared to healthy volunteers. No differences between BPD and schizophrenia patients in facial emotion recognition were also reported by van Dijke et al [13].…”
Section: Recent Behavioral Findingsmentioning
confidence: 93%
“…There is considerable support for a dimensional approach with evidence for a neurobiological overlap of nominally distinct psychiatric disorders on several levels, starting with genes [17,18] and spanning molecules [19], cells [20], brain structure [21,22] and function [23,24], as well as cognitive psychology [25]. And there is also evidence for alterations of brain structure and function associated with psychopathological symptoms in clinically healthy or at-risk patients not meeting the ICD or DSM cut-off [26].…”
mentioning
confidence: 99%
“…The overlap of presumed distinct psychiatric diagnoses have been demonstrated at the genetic (Craddock & Owen, 2010;Smoller et al 2013), molecular (Krishnan & Nestler, 2010), cellular (Swardfager et al 2016), brain circuit (Hulshoff Pol et al 2012;Drysdale et al 2017), pathophysiology (Garn et al 2016) and psychological levels (Catalan et al 2016).…”
mentioning
confidence: 99%
“…The Training for Awareness, Resilience, and Action treatment programme for adolescents proposes subtypes of adolescent depression driven by limbic hyperactivation related to sustained threat (anxious arousal, increased conflict detection, attentional bias to threat, helplessness behaviour, punishment sensitivity and avoidance) with clinical features such as emotional hyper-reactivity, agitation and dysphoric mood (Henje Blom et al 2014). Interestingly, existing trial data, such as the Clinical Antipsychotic Trials of Intervention Effectiveness (Joyce et al 2017) and the Sequenced Treatment Alternatives to Relieve Depression (Chekroud et al 2016;Chekroud et al 2017) have now been re-analysed using a dimensional approach, in an effort to improve tools necessary to implement stratification. The RDoC is not without critics and the incorporation of categorical and dimensional systems is a major challenge within a field with many divisions (Carpenter, 2013).…”
mentioning
confidence: 99%